Instructional leadership and the MERALI strategy for strengthening literacy culture in a rural primary school (IAIN Kendari, 2026)
Strengthening literacy culture in primary schools requires leadership practices that connect instructional improvement, school-based innovation, and evidence-informed decision-making. This study analyses the role of the principal’s instructional leadership in implementing the MERALI strategy to strengthen literacy culture at SD Negeri 2 Banyumudal, while examining the development of literacy indicators from the 2022–2025 Education Report and identifying supporting factors and implementation challenges. Using a qualitative single-case study design, data were collected through semi-structured interviews with the principal, teachers, librarians, parents, and an education office representative, supported by observations and document analysis. The findings show that the principal’s instructional leadership mobilised literacy reform through shared vision, reflective teacher coaching, resource allocation, and community partnership. MERALI operated through four interrelated pillars: restoring a text-rich environment, habituating daily literacy practices, introducing information technology for literacy, and strengthening multi-stakeholder partnerships. Literacy indicators improved consistently, including reading competence, informational text comprehension, reading interest, library use, and parental involvement. The study contributes to literacy leadership scholarship by showing how rural schools can translate data into contextual, sustainable literacy reform. Keywords: data-informed school improvement; Education Report; instructional leadership; literacy culture; MERALI strategy; primary school literacy; rural school